Pattern of ocular trauma in the Western Region of Nepal - Kinderan, YV; Shrestha, E; Maharjan, IM; Karmacharya, S (Nepalese Journal of Ophthalmology, 2012)
Introduction: Ocular trauma is an important cause of unilateral blindness. Objective: To determine the characteristics and visual outcome of ocular trauma in the western region of Nepal. Materials and methods: All cases of ocular trauma presenting in a one-year period to the Himalaya Eye Hospital were retrospectively reviewed. The demographic features, type and cause of trauma, time lapse before presenting to the hospital, management and results were noted. Results: Eleven hundred eyes of 1,069 patients (31 bilateral injuries) were included in this study. Males were predominantly affected (69.3 %) compared to their female counterparts. The average age of the patients presenting with trauma was 28.3 years. On reviewing the causes of trauma, blunt trauma which accounted for 56.5 % was the commonest of all, followed by sharp injury accounting for 16.7 %. The commonest type of trauma was closed globe injury (73.3 %). The visual outcome was poorer in open globe injury as compared to closed globe injury. Of the total cases, only 52.9 % presented to the hospital within 24 hours. Over 7 % of them presented as late as one week. Among these patients, 74.8 % of them had regained normal vision (6/18) and 8 % of the total became blind (<3/60) according to the WHO criteria. Conclusion: Males are more prone to ocular trauma than the females. Open globe injury and late presentation are probably the worst prognostic factors for the visual outcome. There is a need of educating the community regarding the importance of seeking immediate medical care after ocular trauma in a country like Nepal. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5843 NEPJOPH 2012; 4(1): 5-9